[Translated article] Facial Discoid Dermatosis. A 13-Case Series - B. Butrón-Bris; C. Buján; S. Berenguer-Ruiz; L. Martos-Cabrera; P. Rodríguez-Jiménez; J. Fraga; C. Eguren; R. Serrano-Pardo; P. Iranzo; José M. Mascaró, Jr.; M. Llamas-Velasco; A. Reolid (Actas Dermo-Sifiliográficas)
Facial discoid dermatosis (FDD) is a condition characterized by papules-plaques primarily affecting the face. FDD has been associated with psoriasis, seborrheic dermatitis, and pityriasis rubra pilaris. We conducted a retrospective multicenter study with 13 patients diagnosed with FDD in Spain (2014–2022). Patient demographics, clinical presentations, histopathological findings, and treatment outcomes were collected.FDD shows as erythematous-orange, nummular papules and/or plaques with dry scales that primarily affect the facial region. Histopathological analysis revealed a consistent pattern of psoriasiform hyperplasia with confluent parakeratosis, without neutrophils within the epidermal layers.This study provides essential insights into the clinical and histopathological features of FDD within a predominantly Caucasian patient cohort. The presence of distinct clinical features and consistent histological findings underscores the uniqueness of FDD. However, the variability in histological features and persistence of lesions despite various treatments highlight the need for further research to better understand the pathogenesis of FDD and develop effective therapies. Resumen: La dermatosis discoide facial (DDF) se caracteriza por la presencia de pápulo-placas principalmente faciales. Se ha relacionado con la psoriasis, la dermatitis seborreica y la pitiriasis rubra pilaris. Este estudio retrospectivo y multicéntrico incluyó a 13 pacientes diagnosticados de DDF en España (2014-2022). Se recopilaron datos demográficos, clínicos e histopatológicos, así como resultados del tratamiento.La DDF se manifiesta con pápulas y/o placas eritemato-anaranjadas, descamativas, numulares, localizadas predominantemente en la región facial. El análisis histopatológico reveló un patrón de hiperplasia psoriasiforme con paraqueratosis confluyente, sin neutrófilos en las capas epidérmicas.Este trabajo proporciona información sobre las características principales de la DDF en una cohorte mayoritariamente caucásica. La presencia de signos clínicos distintivos y hallazgos histológicos constantes resalta su singularidad. No obstante, la variabilidad histológica y la persistencia de las lesiones, a pesar de diversos tratamientos tópicos, subrayan la necesidad de investigaciones adicionales para comprender su patogénesis y desarrollar terapias efectivas.